The search for formal electrostatic effects on molecular conformation and crystal packing: crystal structure of 2, 2′′‐disubstituted (H versus PPh2) 1, 1′‐(1, 2‐phenylene)bis(3‐methyl‐1H‐imidazol‐3‐ium) bis(trifluoromethanesulfonate). Issue 3 (19th February 2016) - Duhayon, Carine; Canac, Yves; Dubrulle, Laurent; Maaliki, Carine; Chauvin, Remi
Abstract : The conformations of the dications 1, 1′‐(1, 2‐phenylene)bis(3‐methyl‐1 H ‐imidazol‐3‐ium) and its 2, 2′‐bis(diphenylphosphanyl) analogue, and their interactions with neighbouring trifluoromethanesulfonate anions are analyzed from the standpoint of formal electrostatic effects. Neither cation exhibits any geometrical strain induced by the intrinsic repulsion between the positive charges. In contrast, the relative orientation of the imidazolium rings is controlled by different configurations of the interactions with the closest trifluoromethanesulfonate anions. Abstract : Electrostatic interactions between localized integral charges make the stability and structure of highly charged small and rigid organics intriguing. Can σ/π‐electron delocalization compensate reduced conformational freedom by lowering the repulsion between identical charges? The crystal structure of the title salt, C14 H16 N4 2+ ·2CF3 SO3 −, (2), is described and compared with that of the 2, 2′′‐bis(diphenylphosphanyl) derivative, (4). The conformations of the dications and their interactions with neighbouring trifluoromethanesulfonate anions are first analyzed from the standpoint of formal electrostatic effects. Neither cation exhibits any geometrical strain induced by the intrinsic repulsion between the positive charges. In contrast, the relative orientation of the imidazolium rings [ i.e. anti for (2) and syn for (4)] is controlled by different configurations of the interactions with the closest trifluoromethanesulfonate anions. The long‐range arrangement is also found to be specific: beyond the formal electrostatic packing, C—H…O and C—H…F contacts have no definite `hydrogen‐bond' character but allow the delineation of layers, which are either pleated or flat in the packing of (2) or (4), respectively.